1998
DOI: 10.1007/s002590050207
|View full text |Cite
|
Sign up to set email alerts
|

Activity of iodine-123 metaiodobenzylguanidine in childhood neuroblastoma: lack of relation to tumour differentiation in vivo

Abstract: Neuroblastoma (NB) tumour cells have a remarkable tendency to differentiate spontaneously or under the influence of certain drugs. It is not clear whether metaiodobenzylguanidine (MIBG) uptake correlates with differentiation of NB cells. In 28 tumours of 26 patients, iodine-123 MIBG uptake in primary NBs was studied in relation to tumour differentiation, tumour size, cell density and degree of necrosis in subsequently resected specimens. Genetic features such as the presence of chromosomal aberrations (1p-dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…As an exploratory secondary analysis unadjusted for multiple statistical testing, it is also possible that this association is a chance finding and therefore requires replication by other groups. We note that one previous report did not detect a difference in clinical MIBG avidity according to tumor MYCN status [31]. In addition, response rates after high-dose 131 I-MIBG therapy do not appear to differ between patients with MYCN amplified and MYCN nonamplified tumors, though all patients were required to have MIBG avid tumors to receive 131 I-MIBG therapy [32].…”
Section: Discussionmentioning
confidence: 55%
“…As an exploratory secondary analysis unadjusted for multiple statistical testing, it is also possible that this association is a chance finding and therefore requires replication by other groups. We note that one previous report did not detect a difference in clinical MIBG avidity according to tumor MYCN status [31]. In addition, response rates after high-dose 131 I-MIBG therapy do not appear to differ between patients with MYCN amplified and MYCN nonamplified tumors, though all patients were required to have MIBG avid tumors to receive 131 I-MIBG therapy [32].…”
Section: Discussionmentioning
confidence: 55%
“…It should be noted, however, that the disappearance of MIBG is possible in patients with neuroblastoma even without intervention. Late disappearance of MIBG can be observed due to loss of MIBG avidity by the tumor, as well as technical factors that can modify MIBG uptake (21). At the time of study entry, this patient's bone marrow showed one neuroblastoma cell per 100,000 cells by immunocytochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…MIBG is an analog of the adrenergic norepinephrine neurotransmitter, which is taken by the adrenergic origin of NBL and pheochromocytoma using the type 1 cathecolamine uptake mechanism for transport into tumor cells17). Uptake of 123 I-MIBG was highly variable in vivo, and probably influenced by multiple factors such as degree of differentiation in neuroendocrine tumor, interfering medication, and change in the metabolism of the malignant cells due to altered biology13,20). 18 F-FDG, similar to glucose, is transported to within the cells via the GULT (glucose transporters) and intracellular phosphorylated by hexokinase into glucose-6-phosphate and 18 F-FDG-6-phosphate.…”
Section: Discussionmentioning
confidence: 99%